Perancangan UI/UX Pada Website UMKM Cigadung Menggunakan Pendekatan HCD (Human Centered Design) - KURNIAWAN, OKI; HERMANA, ASEP NANA (e-Proceeding FTI, 2024)
The development of information technology is currently increasing. Information technology makes everything easier and cheaper. Every company that wants to expand its marketing reach must have a website, which is a vehicle for promotions and transactions for the company. Small and medium enterprises (SMEs) as part of the form of business in Indonesia should utilize information technology for the advancement of their business. At present the high number of layoffs caused by the Covid-19 situation has made Indonesian people lose their jobs and finally try their luck to become small and medium business actors. User Interface Design is the science of the graphical layout of a web or application. Based on what they do, UX designers are people who create useful products and visualize user flow into tested and beautiful product designs. Based on the problems above, this research created a UI/UX design website platform concept called UMKM Cigadung. The goal is to optimize sellers in conducting transactions and introducing their products through digital platforms. Abstrak Perkembangan teknologi informasi saat ini sangat meningkat. Teknologi informasi membuat semua hal menjadi lebih mudah dan murah. Setiap perusahaan yang ingin memperluas jangkauan pemasarannya pasti mempunyai website, yang menjadi wahana promosi maupun transaksi bagi perusahaan. Usaha kecil menengah (UKM) sebagai bagian dari bentuk usaha di Indonesia seharusnya memanfaatkan teknologi imformasi demi kemajuan usahanya. Saat ini tingginya angka PHK yang diakibatkan oleh situasi covid-19 membuat masyarakat Indonesia kehilangan pekerjaan dan akhirnya mencoba peruntungan menjadi pelaku usaha kecil dan menengah. Perancangan User Interface adalah ilmu tentang tata letak grafis suatu web atau aplikasi. Berdasarkan apa yang dikerjakan, desainer UX adalah orang yang membuat produk yang bermanfaat dan memvisualisasi user flow menjadi desain produk yang teruji dan indah. Berdasarkan permasalahan diatas, penelitian ini membuat konsep platform website perancangan UI/UX bernama UMKM Cigadung. Tujuannya mengoptimalkan penjual dalam melakukan transaksi maupun mengenalkan produk - produknya melalui platform digital.